The social organization of the Asian weaver ant colonies: A natural enemy novel sub-castes worker's functional activity findings. - Moïse Pierre Exélis; Rosli Ramli; Roslinazairimah Zakaria; Azarae Hj Idris; Zubaidah Ya'cob; Rabha W Ibrahim; Salmah Yaakop; Nurul Wahida Othman (PLoS ONE)
An arboreal ant species by nature, the Asian weaver ant Oecophylla smaragdina F., (Hymenoptera: Formicidae) colony's social structure composition was investigated in depth. Brood and barrack nests were collected from the African oil palm (Elaeis guineensis) canopies and Limau kasturi (Citrus microcarpa) orchards, and dissected. All caste's morphological traits were examined stereo-microscopically. The workers' width and length measurements of the separately dissected head, thorax, frontal view, abdomen, and body full side view sizes were recorded. All colonies comprise a founding queen laying thousands of eggs stored in a protective yellowish, unknown sticky substance (shining reflection), with reproductive winged green and newly emerged yellow queens, adult drone males, and wingless workers along their immature pupae and larvae arranged in woven, solid silken chambers (brood nests exclusively). Besides the traditionally known caste of minor and major workers, five polymorphic individuals comprising two unidentified novel sub-castes of intermediate workers and one sub-caste of major workers were described. The full body and abdomen lengths are proposed as dominant predicting factors differentiating among the five sub-castes. The discovery of a multimodal size frequency distribution model contrasts with the classical archetypical bimodal systems in ants. Intermediate workers foraging outside the nest revealed reconnaissance autonomy and aggressive behaviors that aided larger workers in securing the territorial perimeter. Bigger workers occupied the first defensive layers of the colony's territorial frontier, while the intermediate workers maintained their stance at a closer nest distance. Major workers systematically acted as leaders-supervisors by removing individuals of smaller size during overheating exposure. Due to their short lifespan and segregated nests, it is difficult to collect adult males in wide plantations. A stable and average mature three-year-old colony produces several reproductive individuals monthly. The mean number of emerging queens is higher in older colonies (scarcity of males) and lower for younger colonies (queens-males averages are correlated). The queen production increases with higher rainfall and relative humidity. This study identified three novel worker sub-castes: one major intermediate, two intermediate in size. These findings contribute to a better understanding of the overall worker's functional activity. The Asian weaver ant demonstrates adaptive measures in response to challenging abiotic factors (temperature), defying classical labor division rules.